(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Some Organometallic Complexes of La (III), Ce (III), Nd (III), and Gd (III) with mixed Ligand of Uracil and L-ascorbic acid and its isopropylidine derivative were synthesized. Uracil complexes were prepared with some of the inner transition metals in a stoichiometric ratio of (1:1 v/v) (Mn+: L), where M3+ = La (III), Ce (III), Nd (III) and Gd (III) ions. The Complexes were characterized by the physicochemical and spectroscopic techniques as electric conductivity, metal contents, IR, UV–Visible, 1HNMR C13NMR, Mass Spectroscopy and molar conductance techniques. The stoichiometric ratios of the synthesized complexes were confirmed by using molar ratio method. The dissociation constant of Uracil ligand was determined spectro-photometrically. Solvent effect on the electronic spectra of the Uracil ligand was examined using solvents with different polarities. In addition, biological activity of the synthesised metal complexes against Salmonella typhi, Escherichia coli, Staphylococcus aureus and Klebsiella pneumonia bacteria and Aspergillus niger, Aspergillus flavus, Fusarium oxisporium and Trichoderma viride fungi respectively were examined in-vitro.